PENGGUNAAN METODE THINK TALK WRITE (TTW) UNTUK MENINGKATKAN HASIL BELAJAR BAHASA INDONESIA KELAS VIII–F SMP NEGERI 1 RANCAEKEK - Herlina, Lien (P2M STKIP Siliwangi, 2021)
The focus problems of this study is the result of students learning process in Bahasa Indonesia subject still low. From the first study in this class is found some indicator that the students are low especially in the result of Bahasa Indonesia lesson. The purpose of this study is to find how to improve students learning result in Poetry Material Especially in Bahasa Indonesia lesson using Think talk write   Learning Model. The subject of this study is VIII-F Grade at SMP Negeri 1 Rancaekek. They are 24 students include. There are two cycle in this study. Based on the result of this study in cycle 1 the students who got the KKM Score is 32 %. While in the result of cycle 2 is 90 % the students who got KKM score. So that the result of this study using Think talk write   model is success.